ANALISIS PENGARUH PENDIDIKAN DAN PELATIHAN PERKOPERASIAN TERHADAP PELAYANAN KOPERASI KEPADA ANGGOTA SE-KECAMATAN UKUI KABUPATEN PELALAWAN - Istiqomah Istiqomah '; Rina Selva Johan Selva Johan; Hendripides Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to examine the effect of Education and training for Service Cooperative. The population used in this study there are 42 cooperative management 15 cooperative at Subdistrict Ukui, Pelalawan, the sample in this study were 36 cooperative management, type of data used is quantitative. Data analysis technique using multiple linear analysis, t test and f test with significance level of 0,05%. The result showed that the education and training simultaneously affect the service. Based on the partial results of the study showed education no significant effect on the service, meanwhile training significant effect on the service. The coefficient of determination shows that the education and training care service affect 65,1% and the remaining 34,9% are not described in this research model.Keywords: Education, Training and Service